Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Please answer below :-)

Please Answer Below class=

Sagot :

towl35

Step-by-step explanation:

[tex] \frac{2x - 1}{4} + \frac{x}{3} = 2[/tex]

find a common denominator of 12 for each fraction

[tex] \frac{3}{3} \times \frac{(2x - 1)}{4} + \frac{4}{4} \times \frac{x}{3} = \frac{12}{12} \times \frac{2}{1} [/tex]

[tex] \frac{6x - 3}{12} + \frac{4x}{12} = \frac{24}{12} [/tex]

[tex] \frac{6x - 3 + 4x}{12} = \frac{24}{12} [/tex]

[tex] \frac{10x - 3}{12} = \frac{24}{12} [/tex]

multiply both sides by 12

[tex]12 \times \frac{10x - 3}{12} = \frac{24}{12} \times 12[/tex]

12s cancel out

[tex]10x - 3 = 24[/tex]

add three to both sides

[tex]10x - 3 + 3 = 24 + 3[/tex]

[tex]10x = 27[/tex]

divide both sides by 10

[tex] \frac{10x}{10} = \frac{27}{10} [/tex]

The tens on the left side cancel

[tex]x = \frac{27}{10} = 2.7[/tex]